Prediction-Based Planning in Production System Management through Subsystem Interaction - Mikhail Sadiakhmatov; Leonid Mylnikov (Proceedings of the International Conference on Applied Innovations in IT, 2018)
The research concerns the investigation of predictive models based on optimal control task. It allows increasing the management efficiency due to joint consideration and synchronization of internal and external processes towards the system. In this paper, the predictive model for solving multicriterion product management task was developed. To develop a model, automotive industry data was processed. The paper follows the reflexive approach and provides an application of simulation modelling to solve jointly the optimization problem taking into account the mutual influence of the production subsystems. The feasible solutions were received as functions of time. The solutions obtained were compared with the practical ones that based on historical data. The practical significance of the research lies in using market data to estimate company capabilities preliminarily whether they meet the market needs. At the same time, the objectivity of strategic decisions is increasing due to the formalization of process description, objective data preparation, and the company synchronization with the external environment.